(untitled) (Journal of the College of Basic Education, 2022)
The process of analyzing the directorial visions formed for the joints of the theatrical performance and their overlap depends on a number of principles and procedures that require selection, disassembly and installation, in order to create a dialogue network of concerted methodological lines that give the analysis its complementarity, and the axis that accommodates this methodological vision must be derived from recent methodological transformations It comprehends the categories of “the science of the text” and “the science of discourse,” which stem from a holistic and comprehensive view, directed by a systematic awareness that reveals the necessity of linking the knowledge emanating from the propositions themselves, at the moment of working on them, with their qualitative, theoretical and methodological framework.